The Relationship between Patient Comfort and Service Satisfaction in Primary Accredited Health Centers in Lubuklinggau City - Jeannita Sri Agustini Purba; M. Zulkarnain; Misnaniarti Misnaniarti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Health services at Community Health Centers include outpatient services in the form of observation, diagnosis, treatment, and other activities, and inpatient services, which include observation, treatment, diagnosis, treatment, and other medical services where patients are treated for a minimum of 1 day. The purpose of this study was to analyze the relationship between patient comfort and service satisfaction in primary accredited community health centers. This study is an analytic observational study with a cross-sectional design. The population in this study is outpatients at the primary accreditation health center. The sample size in this study was 40 respondents, with consecutive sampling taken based on order of arrival until the sample was fulfilled for the study. The results of the study showed that comfort was not good at (65.0%) and satisfaction was poor at 47.5%, and the results of statistical tests obtained showed that there was a significant relationship between comfort and patient satisfaction in health services (0.006 <0.05). Based on the results above, it can be concluded that there is a relationship between comfort and service quality. It is recommended that the management at an accredited health center optimize communication skills in services related to health services, including communication and interaction with the client.